The lusophony in the blogosphere: from the “imagined community” to the “imaginative community” - Macedo, Lurdes (2014)
Publicado em: "Colonialisms, post-colonialisms and lusophonies: proceedings of the 4th International Congress in Cultural Studies". ISBN 978-989-98219-2-7